2013
DOI: 10.1177/0731684412473359
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of flax/epoxy prepregs before and after cure

Abstract: This paper aims to better understand the nature of flax/epoxy hot melt prepreg systems as well as the mechanical properties of their cured composites. Two uncured systems were subjected to thermal gravimetric analysis and compaction experiments. Composites were then produced in an autoclave at pressures of 1, 3 and 5 bars. Void analysis was carried out on the cured laminates by optical microscopy and void contents ranging from below 1% to over 20% were obtained by image analysis. The primary source of voids wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 22 publications
3
21
0
Order By: Relevance
“…The only positive value is offered by tensile stiffness, in which case it might be suggested that the effect of the voids is possibly overwhelmed by the rigidity during tension offered by basalt layers. As a matter of fact, it is suggested that flax fibre composites produced with similar techniques than the one adopted may present a quite considerably large amount of voids, due to variability of crimp characteristics, which may result in resin starvation [28][29].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The only positive value is offered by tensile stiffness, in which case it might be suggested that the effect of the voids is possibly overwhelmed by the rigidity during tension offered by basalt layers. As a matter of fact, it is suggested that flax fibre composites produced with similar techniques than the one adopted may present a quite considerably large amount of voids, due to variability of crimp characteristics, which may result in resin starvation [28][29].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This is in agreement with typical literature values observed for PFRPs (Table 9). Various studies report that the vacuum-infused PFRPs have a low-void volume fraction of 0.5-4.0 % [71,135,152] and prepreg-based PFRPs have a typical void volume fraction of 0.0-4.0 % [158,159], although, it may be as high as 10 % if low-autoclave pressures (\3 bar) are used [158,159]. It is of interest to note that Madsen et al [75] shown that the porosity in hemp yarn reinforced thermoplastics increases linearly (R 2 = 0.98) with the logarithm of the matrix processing viscosity.…”
Section: Composite Manufacturementioning
confidence: 99%
“…Thus, due to their good specific properties, natural fibres could constitute, in particular applications, an interesting alternative to glass fibres [2,3]. Consequently, various natural fibres reinforced polymer composites were the subject of several studies [4][5][6][7][8][9][10][11][12][13][14]. In particular, the effect of natural fibres treatment on the mechanical properties of these composites, the degradation of their mechanical properties in a hygrothermal environment and their different damage modes during the failure process were studied [4,9,11,14].…”
Section: Introductionmentioning
confidence: 99%